Effect of Cooperative Learning Method on the Performance of Mathematics Students in Public Secondary Schools in Rwanda: A Case of Karongi District - Byiringiro, E (African Journal of Education and Practice, 2024)
Purpose: The aim of this paper was to investigate the effect of cooperative learning on on the performance of Mathematics students in public day Schools in Rwanda" A case of Karongi District'. Methodology: Simple random sampling technique was further applied to obtain Mathematics teachers and students of senior 4, 5 and 6, making 783 target students. The study used a sample of 230 respondents from the sampled schools. The collected data was analyzed using descriptive statistics, correlation, and regression analysis through the statistical package for social science (SPSS) version 21. The data collected were analyzed using descriptive statistics and multiple regression. Findings: The results of the findings indicated that the teaching of mathematics via the cooperative learning method was more correlated with the performance of students in Karongi District (r = 0.611; p= 0.000). Multiple linear regression analysis showed that cooperative learning method contributed to 71.9% of variation on the performance, hence plays a vital role in performance of Mathematics students in public secondary schools in Karongi District. Additionally, it was further inferred that cooperative learning method increases positive attitudes toward learning the subject. Unique Contribution to Theory, Policy and Practice: Social constructivism was used. A key factor in social constructivism is that the children's development is enhanced by participating in activities that are slightly above their level of competence with mastery occurring as a result of help from others; which is enhanced as students are given opportunities to teach each other and practice in a social context. Interactions among students are crucial to cooperative learning and it is the interactions that occur in the groups that help to inspire the learning motivation. The study recommended that to promote the implementation of cooperative learning method effectively, Mathematics teachers should attend seminars, workshops and conferences.